Metabolomic Assessment of Acute Cholestatic Injuries Induced by Thioacetamide and by Bile Duct Ligation, and the Protective Effects of Huang-Lian-Jie-Du-Decoction - Wei, Dan-Dan; Wang, Jun-Song; Duan, Jin-Ao; Kong, Ling-Yi (Frontiers in Pharmacology, 2018)
Huang-Lian-Jie-Du-Decoction, a traditional Chinese formula, has been reported to protect liver from various injuries. Two cholestasis models of rats induced by thioacetamide and by bile duct ligation were established and treated with Huang-Lian-Jie-Du-Decoction. Nuclear Magnetic Resonance-based urinary metabolic profiles were analyzed by orthogonal partial least squares discriminant analysis and univariate analysis to excavate differential metabolites associated with the injuries of the two models and the treatment effects of Huang-Lian-Jie-Du-Decoction. The two cholestatic models shared common metabolic features of excessive fatty acid oxidation, insufficient glutathione regeneration and disturbed gut flora, with specific characteristics of inhibited urea cycle and DNA damage in thioacetamide-intoxicated model, and perturbed Kreb's cycle and inhibited branched chain amino acid oxidation in bile duct ligation model. With good treatment effects, Huang-Lian-Jie-Du-Decoction could regain the balance of the disturbed metabolic status common in the two cholestasis injuries, e.g. unbalanced redox system and disturbed gut flora; and perturbed urea cycle in thioacetamide-intoxicated model and energy crisis (disturbed Kreb's cycle and oxidation of branched chain amino acid) in bile duct ligation model, respectively.